2019
DOI: 10.20448/journal.522.2019.51.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Student-Teacher Relationship in Elementary Schools: “My Teacher & I-Child”

Abstract: Empirical evidence from national and international studies suggests that the teacher-student relationship has a great impact on students' academic success, and social and psychological wellbeing. Realizing the importance of this impact, the present study has two main purposes: firstly, to investigate the perceptions of 6-11 year old students in elementary schools in terms of the informational support, emotional support and closeness they receive based on grade level and the demographic characteristics of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…However, some studies have reported mixed findings upon the impact of teacher support on academic achievement in Pakistani universities. In this connection, for example, one study found that in particular group of students, teacher-student relationship was almost independent of academic performance, suggesting that other factors may also play a role (Oz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported mixed findings upon the impact of teacher support on academic achievement in Pakistani universities. In this connection, for example, one study found that in particular group of students, teacher-student relationship was almost independent of academic performance, suggesting that other factors may also play a role (Oz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2012) found that female instructors are more empathetic with students, reflecting on student engagement levels and outcomes. Conversely, Oz (2019) reported that the faculty's gender does not significantly influence student–faculty rapport.…”
Section: Students’ Perceptions Of Fsrmentioning
confidence: 99%
“…These unique connections also enabled open classroom discussions and student engagement, thereby causing interest to increase rapidly. A robust FSR in the classroom supports students emotionally by promoting self‐assurance and self‐esteem (Oz, 2019).…”
Section: Students’ Perceptions Of Fsrmentioning
confidence: 99%
“…However; after synthesizing 119 studies, which were conducted in the US, Canada, Philippines, Brazil, Germany and the UK in the years from 1948 to 2004, Cornelius-White ( 2007) concluded that the views of STR of the students and observers were actually more predictive of the students' success. Despite the importance of understanding the internal judgments of children in terms of relationships (Lynch & Cicchetti, 1997;Olson, 1977;Reid, Landesman, Treder, & Jaccard, 1989), few studies focused on the student perceptions (Mantzicopoulos & Neuharth-Pritchett, 2003;Murray et al, 2008;Oz & Dolapcioglu, 2019;Williams, 2012). Additionally, there is a scarcity of research that focuses on the STR through the entire elementary school period (Baker, 2006).…”
Section: Student-teacher Relationship (Str)mentioning
confidence: 99%
“…The MFF-C scale was adapted to the Turkish culture by Oz and Dolapcioglu (2019). Since the adapted form of the scale only focused on the STR, it was renamed 'My Teacher and I-Child Scale (MTI-C)' to fit the scale's content.…”
Section: My Teacher and I-child Scale (Mti-c) The My Family And Frien...mentioning
confidence: 99%